Tanggung Jawab Pelaku Usaha Atas Overclaim Sun Protection Factor (SPF) Pada Produk Tabir Surya X - Nabilla Dhinggar Arumbi; Sapto Hermawan; Asianto Nugroho (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2024)
The high public demand for sunscreen creates business opportunities for entrepreneurs. However, due to this substantial demand, it cannot be denied that some business actors resort to deceptive practices to maximize profits. This includes distributing sunscreen with exaggerated SPF claims or overclaiming SPF, indicating that the lab test results differ from what is stated on the label. The research method employed is qualitative, with a normative-empirical type of juridical research. The findings reveal that overclaiming constitutes a violation of consumer rights under Article 4 of the UUPK. Additionally, business actors infringe upon other provisions, namely, Articles 7, 8, and 17 of the aforementioned law. The responsibility of business actors for SPF overclaims is outlined in Article 19 of the UUPK, compelling them to compensate consumers for resulting damages. This serves as an implementation of Liability Based on Fault and Product Liability.